Securing our nation : a collection of speeches 2006-2011 (The Ministry GY, 2011)
Presents a collection of speeches made by the Hon. Clement J. Rohee, MP, Minister of Home Affair, Guyana between 2006 to 2011.
Keywords: SPEECHES